Seropositivity of Anti-Rubella Antibodies as A Marker for Rubella Infection in Infants at High Risk of Congenital Deafness - Nyilo Purnami; Risa Etika; Martono Martono; Puspa Wardhani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Hearing loss in newborns or congenital deafness can be caused by the development of several parts of the auditorysystem. Congenital deafness is often associated with infections, such as Toxoplasmosis, Rubella, Cytomegalovirus (CMV),and Herpes (TORCH). Deafness is very difficult to be early detected. Therefore, simple but fast methods are needed. Earlydetection is based on the Newborn Hearing Screening (NHS) program. Otoacoustic Emission (OAE) and AutomatedAuditory Brainstem Response (AABR) checks are raw materials for early detection. Congenital deafness often occurs withpregnancy infections with viruses such as Rubella. Rubella infection during pregnancy, especially during the first trimester,often causes Congenital Rubella Syndrome (CRS). Rubella infection often occurs with other causes, such as Toxoplasma,CMV, and Herpes. A Serological test can be used as one of the diagnostics of this infection. This study used single RubellaIgG and IgM antibodies and double antibodies test as a marker for the infection. The authors wanted to correlate theserological examination of this infection with the auditory function. Rubella infection was detected with single serologicalanti-Rubella IgG and IgM and double multiple Rubella and TORCH serological tests. Also, the auditory function wasassessed using the OAE and AABR test in this research. The result showed 35 (77.7%) patients with positive Rubellaserological tests among 45 NICU patients at Dr. Soetomo Hospital. There were number of patients was 12 (34.2%) patientswith a single positive serological test and 23 (65.7%) patients with positive multiple TORCH serological tests. The number ofpatients with Rubella negative infection was 10 (22.2%). There were 11 (31.4%) patients of positive Rubella infections withpositive hearing loss and 24 (68.6%) patients with negative hearing loss. From the results of the study, 35 patients were athigh risk of disturbance and the statistical analysis showed that there were no significant serological differences in Rubellapositive with hearing loss (p=0.087). Hearing loss in NICU infants has a high risk of factors causing Rubella infection andother related causes. In most Rubella positive serological tests IgG was found, which can be due to maternal factors.Serology tests need to be repeated for confirmation under the surveillance program. How to follow-up the patients anddefine the next laboratory test after six months remain a great challenge. The efforts need to be strengthened in surveillanceprograms.